Quasi-experimental estimates of the effect of class size on achievement in Norway - Edwin Leuven; Hessel Oosterbeek; Marte Rønning (Institute for the Study of Labor (IZA), 2008)
Using a comprehensive administrative database we exploit independent quasi-experimental methods to estimate the effect of class size on student achievement in Norway. The first method is based on a maximum class size rule in the spirit Angrist and Lavy (1999). The second method exploits population variation as first proposed by Hoxby (2000). The results of both methods (and of variations on these methods) are very similar and cannot reject that the class size effect is equal to zero. The estimates are very precise; we can rule out effects as small as 1.5 percent of a standard deviation for a one student change in class size during three years in a row.
urn:nbn:de:101:1-2008050204
Keywords: I2; 330; Class size; educational production; Bildungsniveau; Schule; Klassengröße; Norwegen